Hakikat, instrumentasi, dan praksis demokrasi indonesia berdasarkan pancasila dan uud 1945 - Fadhila, Widiyatul (Maliki Interdisciplinary Journal, 2026)
Indonesian democracy is a comprehensive and intricate form of government that is founded on Pancasila and the 1945 Constitution (UUD 1945). The values found in Pancasila, which act as a framework for national and state affairs, are what make democracy so important. In addition to providing the foundation for the state, Pancasila also acts as an inspiration for setting up a democratic administration. Every precept outlines the fundamental ideas that ought to guide social and political activities. The 1945 Constitution establishes the legal foundation for Indonesia’s democratic process and governs its tools. The general election, or pemilu, is a significant mechanism that enables people to choose their leaders directly. To maintain impartiality and openness, they are supervised by the General Election Commission (KPU) and held on a regular basis. Furthermore, as representatives of the people, legislative bodies such as the House of Representatives (DPR) and the Regional Representatives Council (DPD) are in charge of enacting laws and monitoring governmental policy. Indonesia’s democratic practices are exemplified by political dynamics, such as public participation in the political process. Through a variety of platforms, including as social media, civil society organizations, and public forums, people are becoming more engaged in expressing their thoughts. Despite this, more people are participating in politics. Ideal democracy is still thwarted by corruption, power abuse, and unequal access to knowledge and information. Briefly said, Pancasila and the 1945 Constitution serve as the foundation for the character, tools, and practices of Indonesian democracy. The entire nation must pledge to consistently actualize Pancasila values in all facets of national life in order to establish a high-quality and long-lasting democracy.